1998
DOI: 10.2108/zsj.15.111
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cystine Aminopeptidase (Oxytocinase) Activity in Mouse Serum, Placenta, Uterus and Liver during Pregnancy or after Steroid Hormone Treatments

Abstract: Changes in cystine aminopeptidase (CAP) activity in serum, placenta, uterus and liver in mice under various physiological conditions were examined by enzymatic analysis using S-benzyl-L-cysteine-4-methylcoumaryl-7-amide as a substrate. Changes in serum CAP activity during pregnancy were less remarkable than those reported in humans; the activity was highest at day 13 of pregnancy and lowest at day 17. During the estrous cycle, the serum CAP level was high at diestrus, as high as that at day 13 of pregnancy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
2
7
0
2
Order By: Relevance
“…Using highly purified recombinant protein, we have confirmed in this study that P‐LAP/oxytocinase degraded peptide hormones such as oxytocin and vasopressin which have uterine contractive and vasoconstrictive activities, indicating potential significance of the enzyme in the maintenance of normal pregnancy. Further work in our laboratory aims to elucidate the biological significance of the release of P‐LAP into maternal serum [28], as it has been reported that aminopeptidases belonging to the membrane‐bound M1 metallopeptidase family are often released into serum during pregnancy [29,30] and soluble P‐LAP was detected only in the serum of pregnant women [5].…”
Section: Discussionmentioning
confidence: 99%
“…Using highly purified recombinant protein, we have confirmed in this study that P‐LAP/oxytocinase degraded peptide hormones such as oxytocin and vasopressin which have uterine contractive and vasoconstrictive activities, indicating potential significance of the enzyme in the maintenance of normal pregnancy. Further work in our laboratory aims to elucidate the biological significance of the release of P‐LAP into maternal serum [28], as it has been reported that aminopeptidases belonging to the membrane‐bound M1 metallopeptidase family are often released into serum during pregnancy [29,30] and soluble P‐LAP was detected only in the serum of pregnant women [5].…”
Section: Discussionmentioning
confidence: 99%
“…16 A few studies on non-human animals have shown that PLAP concentration was high during pregnancy in sheep 17 and mice. 18 In many species, estrone-3-glucuronide (E 1 G) and pregnanediol-3-glucuronide (PdG) are abundant metabolites of estrogen and progesterone excreted into urine, which accurately reflect changes in circulating hormones and the maintenance of pregnancy, respectively. [19][20][21] Therefore, it is important to measure the concentrations of these hormone metabolites in urine to assess the endocrinological changes during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on non‐human animals have shown that PLAP concentration was high during pregnancy in sheep and mice . In many species, estrone‐3‐glucuronide (E 1 G) and pregnanediol‐3‐glucuronide (PdG) are abundant metabolites of estrogen and progesterone excreted into urine, which accurately reflect changes in circulating hormones and the maintenance of pregnancy, respectively …”
Section: Introductionmentioning
confidence: 99%
“…IRAP is a type II membranespanning protein such that when at the plasma membrane the catalytic site is extracellular (Keller et al, 1995). The enzyme was initially defined as specifically cleaving the N-terminal amino acid CysXaa-, in which the half-cystine residue is involved in a disulfide loop, notably in oxytocin or vasopressin, but in vitro has also been demonstrated to cleave a range of peptides not containing disulfide loops (Matsumoto and Mori, 1998;Matsumoto et al, 2000). Our preliminary studies indicate that AT 4 ligands are not cleaved by IRAP (R. A. Lew, T. Mustafa, S. Ye, S. G. McDowall, S. Y. Chai, and A. L. Albiston, manuscript submitted for publication).…”
mentioning
confidence: 99%